2021
DOI: 10.1021/jacs.0c09015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Linker Distribution in the Photocatalytic Activity of Multivariate Mesoporous Crystals

Abstract: The use of Metal-Organic Frameworks as crystalline matrices for the synthesis of multiple component or multivariate solids by the combination of different linkers into a single material has emerged as a versatile route to tailor the properties of single component phases or even access new functions. This approach is particularly relevant for Zr6-MOFs due to the synthetic flexibility of this inorganic node. However, the majority of materials is isolated as polycrystalline solids, which are not ideal to decipher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 52 publications
3
73
0
Order By: Relevance
“…20 This versatility in both the metal and the ligand results in the modulation of properties such as the network exibility, which has shown to be fundamental for key properties, as in catalytic applications, 21,22 and indicates the possibility of ne-tuning the properties through a combination of ligands, 23 as reported in other families of MOFs. [24][25][26][27][28][29] However, other ligands that would normally form different structures are challenging to be incorporated into the SOD structure of ZIF-8 through a direct synthesis. In fact, the mixture of such ligands normally induces changes in the topology.…”
Section: Introductionmentioning
confidence: 99%
“…20 This versatility in both the metal and the ligand results in the modulation of properties such as the network exibility, which has shown to be fundamental for key properties, as in catalytic applications, 21,22 and indicates the possibility of ne-tuning the properties through a combination of ligands, 23 as reported in other families of MOFs. [24][25][26][27][28][29] However, other ligands that would normally form different structures are challenging to be incorporated into the SOD structure of ZIF-8 through a direct synthesis. In fact, the mixture of such ligands normally induces changes in the topology.…”
Section: Introductionmentioning
confidence: 99%
“…[49] Then eat PXRD patterns manifest good crystallinity and phase purity of all samples. Thef luorescence confocal images of UiO-67-4Me-NH 2 -38 % crystals with different sizes verify the homogeneous distribution of the mixed linkers across the whole crystal [50] (Supplementary Figure 15). Therefore,afamily of porous MOFs of UiO-67 prototype are obtained, and their octahedral-cage based pore-nanospaces are post-engineered and modified through fine tuning and mixing of functional groups with distinct hydrophilic/hydrophobic characters (Figure 2).…”
Section: Resultsmentioning
confidence: 65%
“…In general, the solvothermal route is considered to be an efficient strategy to prepare MOFs and their composites‐based photocatalysts because of the high yield, easy operation, low temperature as well as low pressure. [ 71–73 ] In the solvothermal reaction process, choosing a suitable solvent is very important. Up to now, lots of organic‐solvents are employed to fabricate MOFs and their composites, including N , N ‐dimethylformamide (DMF), [ 74–76 ] N , N ‐diethylformamide (DEF), [ 77,78 ] dimethylsulfoxide (DMSO), [ 79–81 ] toluene, etc.…”
Section: The Synthesis Strategies Of the Mofs And Their Composites‐based Photocatalystsmentioning
confidence: 99%
“…In addition, many reports also demonstrated that the MOFs and their composites with different sizes (length, width or diameter) and morphologies can be synthesized through the solvothermal method, for instance, the polyhedral PCN‐250‐Fe 3 with a size of ≈13 µm, [ 72 ] the octahedral Uio‐68 and Uio‐68‐TZDC with the sizes from 10 to 20 µm, [ 73 ] the octahedral Co‐MOFs and Ni‐MOFs composite with an average size of ≈200 nm, [ 74 ] the rod‐shaped MIL‐53(Fe) with the length of ≈50 µm, [ 75 ] the octahedral MIL‐100(Fe) with the sizes from 100 to 200 nm, [ 79 ] etc.…”
Section: The Synthesis Strategies Of the Mofs And Their Composites‐based Photocatalystsmentioning
confidence: 99%